The role of the tutorial system in enabling student academic success - Layton, Delia Melanie (South African Journal of Higher Education, 2016)
A worrying trend in South Africa has been the high attrition rate for first time university students. At the University of Johannesburg (UJ), one intervention to address this low throughput rate is the tutorial system. While it is important to broaden formal access to universities, it is also crucial to provide first year students with access to the epistemologies of their discipline to ensure their academic success. This can potentially be enabled through the tutorial system. While tutorials are growing in size due to increased numbers, the tutorial still has a role to play in giving students the opportunity to engage with each other and their tutor in a smaller group than that of the lecture. For the tutorial to enable student academic success, however, tutors need to support their students not only in their acquisition of the target epistemologies, but to also take cognisance of their students’ ontological needs. Keywords: Academic Success; Throughput rate; Formal Access; Epistemological Access; Ontological Access; Tutorial System.